The efficacy of combined lateral and anterior quadratus lumborum blocks in postoperative pain management following pelvic tumor resection: a randomized controlled trial - Xinrui Yin; Xue Tian; Bingyi Wang; Yi Yang; Xiaodong Tang; Yi Feng; Luyang Jiang (Journal of Orthopaedic Surgery and Research)
Abstract Background A wide range of pain management techniques have been investigated following pelvic tumor resection and reconstruction surgery; however, the optimal components remain a subject of debate. In this prospective randomized controlled trial, we assessed the postoperative analgesic efficacy of integrating lateral quadratus lumborum block (Lateral-QLB) and anterior quadratus lumborum block (Anterior-QLB) with multimodal analgesia (MMA) regimen, compared to MMA regimen alone, in patients undergoing pelvic tumor resection and reconstruction. Methods A total of 56 patients were randomly allocated to either the QLB group (n = 28) or the No Block group (n = 28). The QLB group received an ultrasound-guided Combined quadratus lumborum block (a combination of Lateral-QLB and Anterior-QLB), with 20 mL of 0.375% ropivacaine administered on each approach. The No Block group received standardized multimodal analgesia. Both groups followed an identical postoperative patient-controlled intravenous analgesia protocol. Outcomes included opioid consumption (intravenous morphine milligram equivalents, IV MME) at multiple time points within 48 h postoperatively, time to first opioid request, resting/activity-related pain scores, postoperative neurological assessments (lower extremity motor and sensory function), recovery quality quantified using QoR-15 (Quality of Recovery-15) scores on postoperative days (POD) 1, 2, and 7, and chronic pain prevalence during a 3-month follow-up. Results The QLB group exhibited significant reductions in cumulative IV MME at 24 h (18.56 ± 6.63 vs. 24.29 ± 5.69 mg, p = 0.001) and 48 h (27.87 ± 9.95 vs. 41.29 ± 9.67 mg, p < 0.001), along with an extended time to the first opioid request (median 5.0 vs. 4.0 h, p = 0.005). Resting/activity pain scores were consistently lower (p = 0.008/p = 0.003), accompanied by transient sensory changes in the abdomen/thigh without motor impairment. QoR-15 scores significantly favored the QLB group (p < 0.05), with lower chronic pain rates at 3 months post-surgery compared to the No Block group (7.1% vs. 32.1%, p = 0.021). Conclusion The ultrasound-guided QLB demonstrated superior analgesic efficacy and reduced morphine consumption compared to patients without the block. Our findings provide evidence supporting the hypothesis that QLB is an effective component of multimodal analgesia for individuals undergoing pelvic tumor resection and reconstructive surgery.